Los movimientos civiles ecuatorianos durante el segundo periodo de Rafael Correa - Peñaherrera Oviedo, Andrés Sebastián (2016)
The following graduation paper has as main objective, to demonstrate the existence of repression against civilian groups as a preponderant characteristic of the second period of government of Rafael Correa. By making a comparison between three emblematic cases in which the use of torture, the delegitimization and the media attack were the tools against the civil movements. It will be addressed, the following cases: the 10 of Luluncoto, the torture done to the 60 of the Mejía and the closing of Pachamama Foundation. These three cases represent a sample of a living reality in our country: the criminalization of the social protest and the repression against civilian movements. The use of police force and a delegitimization speech are the main tools used by the government. Nevertheless, there are other tactics used by the government, as it is, the creation of legal instruments that limit the action of collectives. For instance, the creation of the Decree 739 (better known as Decree 16) which grant enormous powers to the authorities and gives them arbitrariness of eliminating civilian organizations if they break any consideration the authority has. For the investigation, it has been used the theory of the securitization since it allows to highlight the actions made as emergency legitimated measures to ensure national security. This reflects human rights abuses such as the freedom of movement, of expression and association. Finally, this paper shows logically that these elements are constant within the three proposed cases. In conclusion, there has been a violation of human rights such as freedom of movement, association and expression of civilian actors, as an output of the government towards the protests made that period.